Carbon steel corrosion behaviors in carbonated aqueous mixtures of monoethanolamine and 1-n-butyl-3-methylimidazolium tetrafluoroborate - Ali, Brahim Si; Ali, B.H.; Yusoff, Rozita; Aroua, M.K. (Electrochemical Science Group, 2012)
Recently, aqueous mixtures of alkanolamines and ionic liquids had emerged as potential solvents for CO2 capture. Solubility data of CO2 in aqueous mixtures of monoethanolamine (MEA) and 1-n-butyl-3-methylimidazolium tetrafluoroborate (bmim BF4) are already available in the literature. However, data on the corrosiveness of these new solvents with regards to carbon steel are still scarce. In this work, carbon steel corrosion behavior in carbonated aqueous mixtures of MEA and bmim BF4 was investigated using potentiodynamic polarization and weight loss methods at fixed CO2 loading of 0.55 mol/mol. The corrosion rates were measured for bmim BF4 concentration ranging from 0.1 to 1.0 M and at temperatures of 40 and 80 degrees C. Carbon steel corrosion rates obtained from the two methods are in agreement; and showed that the presence of bmim BF4 in the carbonated solution has reduced the solution corrosivity to carbon steel for carbonated 4.0 M MEA/bmim BF4 system, but increased that of carbonated 2.0 M MEA/bmimBF4 system. Scanning electron microscopy (SEM) images demonstrated that immersed specimens were severely corroded in carbonated 2.0 M MEA/bmim BF4 system. While for carbonated 4.0 M MEA/bmim BF4 system, a protective surface layer was formed as bmim BF4 concentration and temperature increased, respectively.